P-500 How do we talk to teenagers and young adults about fertility? A qualitative study on young peoples' thoughts about fertility. (30th June 2022) - Sylvest, R; Balslev, J; Steenberg, M; Koert, E; Ziebe, S; Schmidt, L
Abstract: Study question: What are teenagers and young adults' attitudes towards learning about fertility, and how do they want to receive fertility information? Summary answer: Young people find it important to learn about fertility from professionals when they are young, and want to hear about fertility in a multifaceted way. What is known already: During the past 30 years women and men in many high-income countries increasingly postpone family formation. It is estimated that 16-26% of the Danish population who want children will experience infertility at some point during their reproductive years. Several studies have shown that women and men tend to underestimate the decline in fecundity with increasing age and overestimate the success rate of medically assisted reproductive technologies. A growing body of research suggests that young people want to know more about fertility, preferably as part of their education. Study design, size, duration: Semi-structured qualitative focus group interviews were conducted with teenagers (age 18-19) and young adults (age 20-26). Data collection is still ongoing. Participants/materials, setting, methods: The study participants (N = 40) were single or cohabiting men and women throughout Denmark. They were between 18 to 26 years old and recruited from both vocational schools and high schools. The interviews were audiotaped, anonymized and transcribed in full. Data were analyzed using qualitative content analysis following the method by Graneheim and Lundman. Main results and the role of chance: Overall the participants found it very important to learn about fertility as a mandatory part of the curriculum at their educations and they wanted to hear about it in a multifaceted way (e.g., social media, podcasts, theatre and personal stories). The participants want to learn about fertility at an early age, so they have the information they need prior to starting their family in the future. They want to feel involved and heard and have the possibility to ask questions. Knowledge should be provided by a professional other than their teacher. They prefer explanations, rather than listing facts. The participants stressed that personal stories and humor are also important when talking with young people about fertility. They feel a conflict between having a healthy lifestyle to take care of their fertility and the behaviour that they believe is a part of being young. Limitations, reasons for caution: The study participants had all chosen to be a part of this study. Hence, the results may not be directly transferred to all young people in regard to attitudes towards how to talk to teenagers and young adults about fertility. Wider implications of the findings: This study contributes to the understanding and implementation of future fertility awareness educational interventions and campaigns targeted to and effective among young people. These findings can be useful in the process of increasing the fertility awareness in this population. Trial registration number: N/A